Plastic and symbolic aspects of byzantine painting in the context of sacred iconography. Evaluating the relationships with artistic anatomy and the structures of compositional geometry - Bogdan MOHOR-OBREJA (Diversitate si Identitate Culturala in Europa, 2025)
The geometric constants in Byzantine iconography represent a particularly fertile interdisciplinary field of research, situated at the intersection of artistic, historical, philosophical and theological dimensions of visual expression. The correlation between poetry and mathematics, between art and geometry, is not coincidental; rather it arises from the fact that these domains each participate, in their own way, in a shared horizon of symbolic thought and intellectual contemplation. They belong to the higher order of spiritual exercise, wherein perception converts into understanding, and formal intuition acquires cognitive value. In the context of the Byzantine icon, geometric constants do not function as mere elements of aesthetic composition but as structures mediating transfigured historical realities, bearing profound theological meaning. They synthesise, through a specific visual language, the full complexity of Revelation, transcending the boundaries of mimetic representation of sacred events and assuming an integral hermeneutic function: historical, moral, dogmatic and eschatological. This iconic presence, although distinct from the empirical reality of the represented subject, cannot be reduced to a mere symbolic recollection. Discussing the harmony of the transfigured body in iconography undoubtedly means affirming an ontological truth specific to the theology of the image. However, it remains imperative to investigate the fundamentals and internal logic that govern this transfiguration, in order to adequately comprehend the ontological and epistemological status of the icon within the Orthodox ecclesial paradigm.